Early Development of an Innovative Nanoparticle-Based Multimodal Tool for Targeted Drug Delivery: A Step-by-Step Approach - Chiara Barattini; Angela Volpe; Daniele Gori; Daniele Lopez; Alfredo Ventola; Stefano Papa; Mariele Montanari; Barbara Canonico (Cells)
Prostate cancer is the most common tumor in men in developed countries and it often responds poorly to conventional treatments. Monoclonal antibody (MoAb) therapy, for this pathology, has grown tremendously in the past decades, exploiting naked and conjugated antibodies to cytotoxic payloads to form antibody drug conjugates (ADCs). Several studies have been carried out conjugating biomolecules against prostate-specific membrane antigen (PSMA), highly expressed in this tumor, to cytotoxic drugs. Nano-based formulations show high potential in targeted drug delivery to enhance the bioavailability of drugs. Our research aimed to evaluate the feasibility of setting up a nanoparticle-based multimodal tool for targeted drug delivery, describing the step-by-step approach and to perform a first screening of these fluorescent PEGylated silica nanoparticles employed in selective cancer cell targeting and killing. These nanoparticles featured a core–shell structure to contemporarily conjugate the antibody and the cytotoxic payload monomethyl auristatin E (MMAE) using a step-by-step approach. We compared the cytotoxic effect of this multimodal nanotool near the antibody-MMAE and free MMAE. We found a lower cytotoxicity effect of the nanoparticle-based construct compared to free drugs, likely because of the preservation of the previously observed receptor-mediated endocytosis. Nanomedicine is confirmed as a powerful alternative to organic drug delivery systems, even if some aspects, such as drug loading efficacy, release, scalable manufacturing and long-term stability, need to be deepened.